Management of Surgically Accessible Lymph Nodes Beyond Normal Resection Planes - deLahunta, Daniel; Nalamati, Surya (Clinics in Colon and Rectal Surgery, 2023)
This article discusses the management of isolated metastatic lymph nodes for colon and rectal cancer. There are traditionally significant differences in how certain regions of lymph nodes for colon and rectal cancer are managed in the East and West. This has led to the development of the lateral lymph node dissection for rectal cancer and extended lymphadenectomy techniques for colon cancer. This article will evaluate the literature on these techniques and what the surgical and oncological outcomes are at this time. In addition, colon and rectal cancers can occasionally have isolated distant lymph node metastases. These would traditionally be treated as systemic disease with chemotherapy. There is consideration though that these could be treated as similar to isolated liver or lung metastases which have been shown to be able to be treated surgically with good oncological results. The literature for these isolated distant lymph node metastases will be reviewed and treatment options available will be discussed.
Keywords: colorectal cancer; isolated lymph nodes; inguinal nodes; para-aortic nodes; lateral pelvic nodes